2017
DOI: 10.1088/1361-6595/aa6c90
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electron kinetics in O2capacitively coupled plasma with the use of a Langmuir probe

Abstract: A Langmuir probe was used to measure various electron plasma parameters in O 2 capacitively coupled plasma. It was shown that the variation in these plasma parameters was due to changes in the electron heating mechanisms as the discharge conditions varied. The so called 'α-γ' mode transition in O 2 plasma (100 mTorr) was identified from the power evolution (30-600 W) of the electron energy probability function (EEPF), electron density (n e ) and effective electron temperature (T eff ). The EEPF evolved from Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…The deviation in plasma temperature causes a nonlinear change in the energy of the ions with increased power. In the figure below shows that the average ion energy reaches maximum RF power at about 75W (11,13,14). with increasing RF power.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The deviation in plasma temperature causes a nonlinear change in the energy of the ions with increased power. In the figure below shows that the average ion energy reaches maximum RF power at about 75W (11,13,14). with increasing RF power.…”
Section: Resultsmentioning
confidence: 90%
“…For example, the stirring energy of argon atoms is 11.8 eV while the ionization energy is 14.6 eV. Besides, the stirring energy should be greater than or equal to the energy of the electronic case in order for the excitation to occur (7,11). Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the variations of fundamental plasma parameters with power we now discuss the variation of key plasma parameters, namely the electron density, electron temperature and electron collision frequency over the power range presented in figure 2 above. Measurements of fundamental plasma parameters for capacitively coupled discharges in O2 for this reactor have previously been reported 12,18 . Kechkar et al 18 reported ne values at 100 mTorr ranging from ~7 × 10 15 m -3 at 50 W to ~6 × 10 16 m -3 at 500 W applied power with corresponding electron plasma frequencies (ωp) 13 ranging from 0.8 to 2.38 GHz.…”
Section: Real-time Monitoring Of Power Variations In the Process Chamber Using Resmentioning
confidence: 99%
“…Measurements of fundamental plasma parameters for capacitively coupled discharges in O2 for this reactor have previously been reported 12,18 . Kechkar et al 18 reported ne values at 100 mTorr ranging from ~7 × 10 15 m -3 at 50 W to ~6 × 10 16 m -3 at 500 W applied power with corresponding electron plasma frequencies (ωp) 13 ranging from 0.8 to 2.38 GHz. The electron temperature (Te) values (at 100 mTorr) ranged from 2.3 eV at 50 W to 0.8 eV at 500 W. Substituting into equation ( 1) above using an O2 mass of 2.6×10 -26 kg for mion, we find the conduction current ranges from 0.214 A at 50 W to 1.1 A at 500 W. To corroborate we compare our calculation with an inline spatially averaged probe measurement measured using a V-I probe (figure 2c 13,18 ).…”
Section: Real-time Monitoring Of Power Variations In the Process Chamber Using Resmentioning
confidence: 99%
“…by extracting the geometric resonance frequency shown in figure 4 and employing an estimate of the total sheath width. A calculation of the high voltage sheath size is carried out by employment of the Child sheath law 22) coupled with a combination of Langmuir probe measurements 13,14) for electron density and temperature and I-V measurements for estimation of the sheath voltage. 27) The 'high voltage' sheath width is estimated here as 0.…”
Section: B(r)mentioning
confidence: 99%